Germline and somatic JAK2 mutations and susceptibility to chronic myeloproliferative neoplasms - Goldin, Lynn R (BioMed Central, 2009)
Myeloproliferative neoplasms (MPNs) are a group of closely related stem-cell-derived clonal proliferative diseases. Most cases are sporadic but first-degree relatives of MPN patients have a five- to seven-fold increased risk for developing an MPN. The tumors of most patients carry a mutation in the Janus kinase 2 gene (JAK2(V617F)). Recently, three groups have described a strong association of JAK2 germline polymorphisms with MPN in patients positive for JAK2(V617F). The somatic mutation occurs primarily on one particular germline JAK2 haplotype, which may account for as much as 50% of the risk to first-degree relatives. This finding provides new directions for unraveling the pathogenesis of MPN.